From Herb to Dessert: Unveiling Swertia chirata's Impact on Orange Jelly Dynamics - Arpita Chowdhury; Meherun Nessa Tuhin; Monsur Ahmad; Md. Fahad Bin Quader (Health Dynamics, 2024)
Background: Foods had a distinctive medicinal role as a remedy for illness for many centuries. The threat of Antimicrobial Resistance (AMR) in all over the world is growing extremely due to the reason that any use of antimicrobials, however appropriate and justified, results in accumulation of resistance. Thus, researchers all over the world are toiling hard to introduce foods that possess therapeutic effects as medicine. Citrus fruits were the first foods to provide a true cure of any illness. The present study was undertaken to develop a value- added product that was hypothesized to bestow numerous dietary properties, to meet the ever growing demands of the consumers. Methods: A strategy was developed to formulate good quality jelly from Orange & Swertia chirata. To develop the jelly different proportions of orange juice & S. chirata namely T1 (95:05), T2 (90:10), T3 (85:15) was formulated and T0 was utilized as control (100% orange jelly). In addition to microbial analysis, phytochemical analysis, physicochemical properties, and sensory evaluation were conducted. Results: The physico-chemical properties of the formulated jellies were in alignment with previous studies. The results of the microbiological analysis were excellent. As, there were no detectable levels of E. coli and Salmonella in the formulation for a period of up to 2 months. The sample T3 exhibited maximum level of total phenolic content (168.3 mg GAE/gm), total flavonoid content (49.1 mg QE/gm) and antioxidant activity (135.63 mg/100gm). Therefore, the bioactive compounds had a high precedence on the sample T3 than the control one. Conclusion: After evaluating all the factors, it can be concluded that creating a value-added product will make it easier to market a product that not only attracts consumers but also possesses concealed medicinal properties.